1990
DOI: 10.1056/nejm199010113231503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Monitoring of Glycosylated Hemoglobin Levels in Insulin-Dependent Diabetes Mellitus

Abstract: Regular measurements of hemoglobin A1c lead to changes in diabetes treatment and improvement of metabolic control, indicated by a lowering of hemoglobin A1c values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(117 citation statements)
references
References 17 publications
4
108
1
2
Order By: Relevance
“…Yet, most experience has centered on blood-lead assessment, where this exposure biomarker has been an important outcome variable in many intervention studies (Aschengrau et al, 1994;Hilts et al, 1998;Lanphear et al, 1999). In a wider sense, the use of personal clinicalchemistry results is well established in clinical management of certain diseases, especially serum-glucose monitoring in diabetes patients (Cox et al, 1991;Larsen et al, 1990). Also, cholesterol screening has a long history in the prevention of cardiovascular disease, because a serum result deemed disadvantageous motivates the subject to pursue available means to remain healthy (Elton et al, 1994;Reynolds et al, 1997;Strychnar et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, most experience has centered on blood-lead assessment, where this exposure biomarker has been an important outcome variable in many intervention studies (Aschengrau et al, 1994;Hilts et al, 1998;Lanphear et al, 1999). In a wider sense, the use of personal clinicalchemistry results is well established in clinical management of certain diseases, especially serum-glucose monitoring in diabetes patients (Cox et al, 1991;Larsen et al, 1990). Also, cholesterol screening has a long history in the prevention of cardiovascular disease, because a serum result deemed disadvantageous motivates the subject to pursue available means to remain healthy (Elton et al, 1994;Reynolds et al, 1997;Strychnar et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Larsen et al (141) randomly assigned 240 patients with type 1 diabetes to either a treatment or a control group. GHb testing was performed quarterly in both groups for 12 months; test results were made available, however, only to patients and health care providers in the treatment group.…”
Section: Glycated Hemoglobin Testingmentioning
confidence: 99%
“…Studies have demonstrated that patients who obtain regular clinical tests are more likely to improve poor glycemic levels and achieve metabolic control. [11][12][13] A key focus of diabetes DM programs is motivating members toward healthy behaviors, including obtaining recommended clinical tests. Results of a recent Healthways study demonstrated an association between patient participation in their diabetes DM programs and a measurable improvement in A1c testing.…”
mentioning
confidence: 99%